MANAGEMENT IN PUBLIC AUTHORITIES: THE UKRAINIAN CONTEXT AND THE EXPERIENCE OF THE EU, THE USA AND CANADA - Anatoliy Briatko (Eastern Europe: Economy, Business and Management, 2026)
The relevance of the study stems from the fact that the quality of management in public authorities has become a decisive factor of economic resilience and post-war recovery in Ukraine, as well as a core precondition for the successful completion of the negotiations on the country’s accession to the European Union. The purpose of the article is to substantiate the directions for modernising management in Ukrainian public authorities on the basis of a systematic generalisation of managerial experience accumulated by the member states of the European Union, the United States and Canada. The methodological framework of the research combines comparative analysis of public management models, historical and logical methods, systematisation and synthesis, and the analysis of statistical and analytical data produced by international organisations. The results of the study show that developed countries have gradually moved from the traditional bureaucratic model towards hybrid systems that combine managerial flexibility and performance orientation with the classical values of impartiality, legality and continuity of the civil service. It has been established that the most transferable instruments for Ukraine are strategic planning integrated with medium-term budgeting, performance management built on a limited set of outcome indicators, a professional senior civil service, competency-based human resource management and digital-era governance grounded in an integrated data infrastructure. The practical value of the article lies in the possibility of using its conclusions in the preparation of the new public administration reform strategy of Ukraine for the post-war period and in the design of civil service development programmes.